Vermicomposting of different organic materials using the epigeic earthworm Eisenia foetida - Yvonne Indrani Ramnarain; Abdullah Adil Ansari; Lydia Ori (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose The present research was conducted with the objective of exploring the vermicomposting process, which involves different stages such as building of a vermicompost station; import of a compost earthworm (Eisenia foetida); and production of vermicompost using dry grass clippings, rice straw and cow manure. The vermicompost produced can be of significant value to the end users like farmers for replacement of chemical fertilizers and procuring better prices for the organic produce using such composting material locally available at much lower cost. Methods Vermicomposting was done using Eisenia foetida with three treatments [T1 (Rice straw), T2 (Rice straw + grass) and T3 (Grass)]. Temperature, humidity and pH were measured during the process. The population of earthworms, the production of vermicompost, and the chemical and microbial characteristics of the vermicompost were recorded after sixty (60) days and hundred twenty (120) days. The data were analyzed statistically using Sigma Plot 12.0. Results Results indicated that for all the three treatments the temperature was in the range of 0–35 °C, the humidity was between 80 and 100% and the pH fluctuated in the range of 5.5–7.0 and stabilized to near neutral on the 60th day. The combination of rice straw and grass had the highest rate of vermicompost production of 105 kg/m2 followed by grass and rice straw with 102.5 kg/m2 and 87 kg/m2, respectively, at the end of 120 days. Conclusion The harvested vermicompost had an excellent nutrient status, confirmed by the chemical analyses, and contained all the essential macro- and micronutrients.